Creative (Re)construction and Integration of Knowledge. The Tutoring Method as a Positive, Pro-development Education in an Emancipatory and Feminist Context - Wróblewska, Halina Monika (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
The method of tutoring adopted for the purposes of the study was taken into account due to the context of recognising it as an alternative and personalised form of education. It allows for both a developmental approach (involving both tutor and student) as well as a dialogical and processual approach. The perspective of emancipation is understood as the context of broadly understood change, broadening substantive knowledge, introducing new elements to it in order to expand the perspective. The idea of emancipation in education is expressed in an approach of a strongly individualised nature and methodical change. Contemporary feminist theories create a non-hierarchical space for critical thinking, which can be understood as an engaged co-construction of knowledge with others, motivated by a desire to understand and a need to exchange ideas. The problem of the study in the author’s intention was framed as a research and teaching space with a process character. The aim of the issue in question is to present the educational practice of the tutoring method, which implements the idea of pro-developmental education embedded in an emancipatory and feminist context. The research issues concern: 1) the potential of tutoring in the management of education supporting development; 2) the essence of the feminist context; 3) educational practice showing the emancipatory potential of tutoring; 4) the creative essence of didactic and tutoring work and its results. The research method is a case study of a tutoring project. The basis for the considerations is the author’s own experience – a research and didactic employee of the university in the tutoring programme “Student as Researcher, Scientist, and Discoverer,” carried out in cooperation with the secondary school environment. The implementation of the tutoring programme allowed the students to explore their capabilities, develop their interests and passions. This provided an opportunity to create educational opportunities to demonstrate creativity in finding new, valuable and original solutions to problems through independent, critical thinking and collaboration. The implemented original research project allowed for creative (re)construction and integration of knowledge.